Analisis Komparatif Penerbangan Boeing B-737 dan Airbus A-320 Rute Palembang – Cengkareng Pasca Pandemi Covid-19 - I Made Indradjaja Brunner; Nella Sajida Talfa; Barkah Alif (Fakultas Teknik, 2023)
Aviation activities experienced a strong disruption during the Covid-19 pandemic with restrictions on passenger movement. This article describes a statistical analysis related to flight activity on two types of aircraft, the Boeing B-737 and Airbus A-320, during the end of the pandemic. This research uses the case study method using daily data on the number of passengers, baggage weight, cargo weight, and total fuel needed during the 2021-2022 period. The data is analyzed using descriptive statistics and inferential analysis, namely one-way t-test with the assumption of inequality of variance. The results of the descriptive analysis show that in 2021-2022 there were fluctuations in number of passengers and cargo. Flight activity of the Airbus A-320 is more frequent than that of the Boeing B-737. These results also prove that flight activity on weekends is busier than on weekdays. In addition, the results of the t-test analysis show that there is a significant difference at 95% confidence level between the flight activities of the Airbus A-320 and the Boeing B-737 on the Palembang-Cengkareng departure route at Sultan Mahmud Badaruddin II Airport. This article is also expected to provide an overview regarding the use of statistics to test differences between two variables.